HUBUNGAN SIKAP DAN PERILAKU AKSEPTOR TERHADAP KEPATUHAN KUNJUNGAN ULANG PENGGUNAAN KB SUNTIK 1 BULAN DI TPMB S KABUPATEN KARAWANG 2024 - Iriani, Oktarina Sri; Oktapiani, Santi; Meliyanti, Mira; Suryani, Ida (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
The Family Planning (FP) program aims to control the birth rate, one of which is through the use of the 1-month injectable contraceptive method. This study aims to determine the correlation between acceptors’ attitudes and behaviors with compliance to follow-up visits for the 1-month injectable contraceptive at the Independent Midwife Practice (TPMB) S in Karawang Regency in 2025. This research uses a quantitative approach with a cross-sectional design. The sample consists of all 1-month injectable contraceptive acceptors at TPMB S, totaling 50 respondents using a total sampling technique. Data were analyzed using the chisquare test. The results showed that the majority of acceptors had negative attitudes (68%) respondents 34 and positive behaviors (64%) respondents 32. However, the level of compliance with follow-up visits was very low, with only 8% being compliant. The chi-square statistical test showed no significant correlation between attitudes and visit compliance (p = 1.000), as well as between behaviors and visit compliance (p = 1.000). In conclusion, there is no significant correlation between the attitudes and behaviors of FP acceptors and their compliance with follow-up visits for the 1-month injectable contraceptive at TPMB S in Karawang Regency.